Intermediate MCAD Deficiency Associated with a Novel Mutation of the ACADM Gene: c.1052C>T - Holli M. Drendel; Jason E. Pike; Katherine Schumacher; Karen Ouyang; Jing Wang; Mary Stuy; Stephen Dlouhy; Shaochun Bai (Case Reports in Genetics)
Medium-chain acyl-CoA dehydrogenase deficiency (MCADD) is an autosomal recessive disorder that leads to a defect in fatty acid oxidation. ACADM is the only candidate gene causing MCAD deficiency. A single nucleotide change, c.985A>G, occurring at exon 11 of the ACADM gene, is the most prevalent mutation. In this study, we report a Caucasian family with multiple MCADD individuals. DNA sequence analysis of the ACADM gene performed in this family revealed that two family members showing mild MCADD symptoms share the same novel change in exon 11, c.1052C>T, resulting in a threonine-to-isoleucine change. The replacement is a nonconservative amino acid change that occurs in the C-terminal all-alpha domain of the MCAD protein. Here we report the finding of a novel missense mutation, c.1052C>T (p.Thr326Ile), in the ACADM gene. To our knowledge, c.1052C>T has not been previously reported in the literature or in any of the current databases we utilize. We hypothesize that this particular mutation in combination with p.Lys304Glu results in an intermediate clinical phenotype of MCADD.